Towards a sustainable and near ambient DeNO(x) under lean burn conditions: a revisit to no reduction on virgin and modified pd(111) surfaces - Roy, Kanak; Jain, Ruchi; Gopinath, Chinnakonda S. (ACS Catalysis, 2014)
Catalytic conversion of NO in the presence of H-2 and O-2 has been studied on Pd(111) surfaces, by using a molecular beam instrument with mass spectrometry detection, as a function of temperature and reactants composition. N-2 and H2O are the major products observed, along with NH3 and N2O minor products under all conditions studied. Particular attention has been paid to the influence of O-2 addition toward NO dissociation. Although O-2-rich compositions were found to inhibit the deNO(x) activity of the Pd catalyst, some enhancement in NO reduction to N-2 was also observed up to a certain O-2 content. The reason for this behavior was determined to be the effective consumption of the H-2 in the mixture by the added O-2 and O atoms from NO dissociation. NO was proven to compete favorably against O-2 for the consumption of H-2, especially <= 550 K, to produce N-2 and H2O. Compared with other elementary reaction steps, a slow decay observed with the 2H + 0 -> H2O step under SS beam oscillation conditions demonstrates its contribution to the rate-limiting nature of the overall reaction. Pd(111) surfaces modified with O atoms in the subsurface (Md-Pd(111)) induces steady-state NO reduction at near-ambient temperatures (325 K) and opens up a possibility to achieve room temperature emission control. A 50% increase in the reaction rates was observed at the reaction maximum on Md-Pd(111), as compared with virgin surfaces. Oxygen adsorption is severely limited below 400 K, and effective NO + H-2 reaction occurs on Md-Pd(111) surfaces. Valence band photoemission with a UV light source (He I) under different oxygen pressures with APPES clearly identified the characteristics of the Md-Pd(111) surfaces and PdO. The electron-deficient or cationic nature of Md-Pd(111) surfaces enhances the NO dissociation and inhibits oxygen chemisorption <= 400 K under lean-burn conditions.
Keywords: deNO(x); heterogeneous catalysis; Hydrogen; lean burn; molecular beam; nitric oxide; Palladium; surface modification

Three way catalytic converter reactions aspects at near ambient temperatures on modified pd-surfaces - Roy, Kanak; Jain, Ruchi; Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Comptes Rendus Chimie, 2016)
The dissolution of oxygen in palladium plays an important role in palladium catalysis. The present study shows that the surface modification (SM) due to the dissolution of atomic oxygen into the subsurfaces of palladium can be used as a control to tune its catalytic activity. CO oxidation and NO + H-2 + O-2 reaction was separately carried out on metallic Pd and on surface modified Pd using a molecular beam instrument and the results were compared. The metallic Pd does not show activity below 400 K for both reactions, whereas the SM-Pd shows activity at near-ambient temperatures. The electronic change due to SM was investigated using ambient pressure photoelectron spectroscopy, and the investigation clearly shows the effect of subsurface oxygen in the ambient temperature activity of palladium. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.